Readings in microeconomics - Breit, William; Hochman, Harold M. (New York: Holt, Rinehart and Winston, 1968)
The papers reprinted in this volume focus on the logic, methodology, and applications of microeconomics. In most cases articles that emphasize conceptual rather than empirical materials have been selected. Also included are articles that can be readily understood without significant formal training in mathematics.
Bibliographical footnotes.
rpm 12/10/2017
Loans
Keywords: Microeconomics